The Effect Of Real Earning Management, Earning Quality, And Leverage On Company Performance With Company Age As A Moderation Variable - Ipan Adi Putra; Melinda Malau (Journal Of Social Science (JoSS), 2023)
The purpose of this study is to analyze whether real earnings management, earning quality, and leverage affects companies' performance with company age as a moderation variable. The method used in this study was panel data regression analysis. The sample used in this study consisted of 124 listed manufacturing companies listed on the Indonesian Stock Exchange for the period 2017-2021. As a result, real earning management (ACFO) and real earning management (ADISX) negatively affect company performance, while earning quality positively affects company performance, and company age strengthens the relationship between earning quality and company performance. Company age enhances the relationship between leverage and company performance. This study implies that companies need to limit real earning management because it significantly negatively affects the company's performance, and then the company can increase.